Shiga toxin-associated hemolytic uremic syndrome: effect of sodium butyrate on sensitivity of human umbilical vein endothelial cells to Shiga toxin. - Louise, C B (1995)
Escherichia coli O157:H7-related vascular damage such as hemolytic uremic syndrome is believed to require the Shiga-like toxins. This study demonstrated that sodium butyrate sensitized human umbilical vein endothelial cells to Shiga toxin and increased the expression of Shiga toxin receptor, globotriaosylceramide (Gb3), on human umbilical vein endothelial cells.